Maipomycin A, a Novel Natural Compound With Promising Anti-biofilm Activity Against Gram-Negative Pathogenic Bacteria - Zhang, Junliang; Liang, Xiaoyan; Zhang, Shiling; Song, Zhiman; Wang, Changyun; Xu, Ying (Frontiers in Microbiology, 2021)
Pathogenic bacterial biofilms play an important role in recurrent nosocomial and medical device-related infections. Once occurred, the complex structure of the biofilm promotes the development of antibiotic resistance and becomes extremely difficult to eradicate. Here we describe a novel and effective anti-biofilm compound maipomycin A (MaiA), which was isolated from the metabolites of a rare actinomycete strain Kibdelosporangium phytohabitans XY-R10. Its structure was deduced from analyses of spectral data and confirmed by single-crystal X-ray crystallography. This natural product demonstrated a broad spectrum of antibiofilm activities against Gram-negative bacteria. Interestingly, the addition of Fe(Ⅱ) or Fe(Ⅲ) ions could block the biofilm inhibition activity of MaiA because it is an iron chelator. However, not all iron chelators showed biofilm inhibition activity, suggesting that MaiA prevents biofilm formation through a specific yet currently undefined pathway. Furthermore, MaiA acts as a synergist to enhance colistin efficacy against Acinetobacter baumannii. Our results indicate that MaiA may potentially serve as an effective antibiofilm agent to prevent Gram-negative biofilm formation in future clinical applications.